The Discourse of the Resilience of Hospitals in the Theoretical Context of the Organisation’s Concept of Resilience and Factors - Liukinevičienė, Laima; Blažienė, Jurgita (Socialiniai tyrimai, 2022)
Recovery and resilience, the ability to operate under the conditions of uncertainty – these challenges are now becoming the key tasks for each organisation. The research of the organisation’s concept of resilience is primarily linked to ecological sciences, followed by studies in social sciences linked to vulnerability and resilience of social groups, communities, cities, and organizations as systems. The efforts of scientists to develop the analysis, measurement instruments of resilience, observable resilience indicators systems, indices, regional vulnerability maps, development of regional resilience policies, etc. are visible. Scientists indicate that resilience is a complex ability and process and can be defined differently, depending on the contexts, but all of them are united by the notion that it is a positive effect in preparing for or after challenges, that it must be encouraged (Lee et al., 2016). The organisation’s theoretical concept of resilience is not widely developed and there is a lack of information on how organisations become resilient.The research aims to define the concept of organisation’s resilience, its features and factors as well as to reveal the concept of the resilience of hospitals in the theoretical context of the resilience of the organisation. The following research methods were used: the analysis, generalization and systematization of the content of scientific literature, synthesis of ideas based on scientific analysis.The definition of the concept of organisation’s resilience is based on a previous empirical research conducted by Barasa et al. (2018) as well as on the latest scientific insights:According to Jucevičius et al. (2017), resilience as the ability to regain strength after changes or errors is conceptually different from the concept of robustness, which describes systems that ignore environmental impacts. The resilience of an organization is the intrinsic ability of an organization to maintain and return to a dynamically stable state. It is the maintenance of resources in a sufficiently flexible form to allow them to be spontaneously adapted in the event of an unforeseen threat. Continuous harmonisation of the monitoring of small errors with improvisation provides employees with expert and wider competencies for more flexible adaptation.The idea proposed by Gricevičius (2019) to link the resilience of the organization to the ability to survive and even thrive during a crisis supports the idea of Gečienė and Raišienė (2019, 2020) that the resilience of the organization should be understood more as a capacity and process than a result, and as adaptation rather than stability (Gečienė et al., 2020).Insight into the fact that we are constantly strengthening the resilience of organisations by adapting to changes at three levels: the potential of the resources available in the system, participants in the internal communication system and variables, creative and flexible responses to the challenges (Holling and Gunderson, 2002, cited in Gečienė, 2020); that the resilience of the organisation must be perceived as a long-term goal (Litz, 2005, cited in Gečienė, 2020).Beuran and Santos (2019) consider that three definitions are important in the organisation’s conceptualisation of resilience: resilience as an organisational characteristic; resilience as a result of the organisation’s activities; resilience as an identification of disorders that the organisation can tolerate.The theoretical concept of organization’s resilience is developed by defining external and internal factors of resilience. The external factors of the resilience of public sector organisations include the following: 1) political factors that directly or indirectly influence organisations’ involvement in a greater focus on the organisation’s sustainable development, unforeseen challenges in the long term; 2) economic factors (e.g. availability of financial resources); 3) technological factors (e.g. availability of hardware and software; digital progress), social factors (e.g. decentralisation as management practice in the public sector, coordination of systems, greater awareness of resilience in society, etc.). Disseminating the experience of business organisations in adapting to challenges in the media has also become a social factor.According to scientific practice (Barasa et al. (2018); Gečienė (2020)), to analyse the passive and active resilience of the organisation, we have divided the internal factors of the organization’s resilience into two groups:1. Passive or operational, adaptive resilience of the organisation. The factors are as follows: 1) prudent management of public (physical, economic, organisational, social, human) capital, assets held or entrusted with management; management of organisational change management, absorption, adaptability, reconstruction capacity is essential; 2) a balanced organisational routine and structure; 3) management and continuous improvement of internal information and communication systems; 4) management (managerial) practices; 5) organizational culture.2. Active or planned, strategic, otherwise capability-oriented resilience of the organization. The factors are as follows: 1) the organisation’s resilience planning, strategy; 2) the organisation’s external policy focused on strengthening resilience; 3) continuous involvement in the analysis, application, development of managerial innovations; 4) leadership and continuous improvement of the organisation’s resilience competencies.Hospitals are organisations whose management is subject to the same managerial principles as in budgetary institutions in general, and therefore the analyzed resilience features of organizations are also applicable to hospitals. Due to the specific purpose of organisations (human health is one of the most important values, health care is a constitutionally justified objective and public interest) and relevance during the 2020–2021 pandemic, there is an increase in the discourse of the scientific resilience of the health system, driven also by increased interaction between politicians, scientists and medical professionals. The resilience of the health system and individual health care institutions is becoming a priority objective of public policy, and the issue of resilience is linked not only to post-crisis recovery but also to the active prospect of resilience – to be prepared for future challenges. In addition to adaptive and planned resilience in the discourse of health system, science activates a discussion on the concept of everyday resilience, as hospitals have to deal with unforeseen challenges every day, the consequences of which can affect patients.
Keywords: organizational vulnerability; organizational resilience; hospital resilience